An Analytical Study of Liquidity and Profitability: Analysis of Selected Oil and Gas Companies in India - Priyanka Meghanathi; Alok Kumar Chakrawal (Celebes Scholar pg, 2021)
Two of the most significant KPIs, liquidity and profitability, are used to gauge a company's success. In order to examine the financial health and profitability of selected Indian oil and gas businesses, this study was performed. From 2016-17 through 2020-21, the top five listed firms by market capitalization are Reliance Industries Ltd., Oil and Natural Gas Corporation (ONGC), Indian Oil Corporation (IOCL), Bharat Petroleum (BPCL), and Gas Authority of India Ltd. (GAIL). Four ratios have been used to evaluate the financial and profitability positions of chosen organizations, including the current ratio, the quick ratio, the net profit ratio, and the return on invested capital. An ANOVA with a 5% threshold of significance was employed to test the hypotheses. The study's main conclusion is that Reliance industries Ltd's liquidity and profitability performance is superior to those of other chosen oil and gas firms.